Case Series and Review of Hematological and Non-Hematological Malignancies in Aging Patients with Sickle Cell Disease in the Hydroxyurea Era. (2nd September 2020) - Rizk, Sanaa; Axelrod, David J.; Olaosebikan, Rasaq; Ballas, Samir K.
Abstract: Survival of adult patients with sickle cell disease has increased progressively since the 1970s. Aging patients with sickle cell disease are at risk of developing comorbidities that are not due to sickle cell disease itself, including malignancies. Many studies tried to assess the incidence of malignancy in patients with sickle cell disease. However, no studies have been done to evaluate cancer incidences in aging sickle cell patients, especially in the hydroxyurea (HU) era. In this review, we assessed the prevalence of malignancies in aging patients with sickle cell disease at our institution with or without HU therapy. Retrospective analysis of hospital records identified patients who had been diagnosed to carry sickle cell disease and malignancies before 2020 using the International Statistical Classification of Diseases and Related Health Problems (ICD-10) coding. Four hundred and eighty-three sickle cell disease patients were seen in our inpatients/outpatients offices. Among these, 12 sickle cell disease patients had a confirmed diagnosis of malignancy. The patients were classified into three categories based on age groups: four patients who were 60 years and older had multiple myeloma. Solid tumors were found in 5/6 patients, aged 40–60 who had the Hb S ( HBB : c.20A>T) (β S /β S ) genotype with signs of iron overload. Two patients, aged 25 and 35, had hematological malignancies. The number of patients on HU was too small to make any comment on relationship to malignancy or mortality. This study is only one institution's experience, further investigation on a larger scale is needed to look into cancer incidences in this population.